Low emission zones reduced PM10 but not NO2 concentrations in Berlin and Munich, Germany. (15th January 2022) - Gu, Jianwei; Deffner, Veronika; Küchenhoff, Helmut; Pickford, Regina; Breitner, Susanne; Schneider, Alexandra; Kowalski, Michal; Peters, Annette; Lutz, Martin; Kerschbaumer, Andreas; Slama, Rémy; Morelli, Xavier; et al.
Abstract: Low emission zones (LEZs) aiming at improving the air quality in urban areas have been implemented in many European cities. However, studies are limited in evaluating the effects of LEZ, and most of which used simple methods. In this study, a general additive mixed model was utilized to account for confounders in the atmosphere and validate the effects of LEZ on PM10 and NO2 concentrations in two German cities. In addition, the effects of LEZ on elemental carbon (EC) and total carbon (TC) in Berlin were also evaluated. The LEZ effects were estimated after taking into account air pollutant concentrations at a reference site located in the regional background, and adjusting for hour of the week, public holidays, season, and wind direction. The LEZ in Berlin, and the LEZ in combination with the heavy-duty vehicle (HDV) transit ban in Munich significantly reduced the PM10 concentrations, at both traffic sites (TS) and urban background sites (UB). The effects were greater in LEZ stage 3 than in LEZ stages 2 and 1. Moreover, compared with PM10, LEZ was more efficient in reducing EC, a component that is considered more toxic than PM10 mass. In contrast, the LEZ had no consistent effect on NO2 levels: no effects were observed in Berlin; in Munich, the combination of the LEZ and the HDV transit ban reduced NO2 at UB site in LEZ stage 1, but without further reductions in subsequent stages of the LEZ. Overall, our study indicated that LEZs, which target the major primary air pollution source in the highly populated city center could be an effective way to improve urban air quality such as PM mass concentration and EC level. Graphical abstract: Image 1 Highlights: We successfully applied a statistical model in evaluating the effects of LEZ. LEZ is effective in reducing PM10 concentrations in Berlin and Munich. No effects for NO2 are observed in Berlin; the effects are not consistent in Munich. The effects for PM10 were higher at LEZ stage 3 than stage 2 and 1. LEZ stage 3 is more effective reducing EC (24.9%) and TC (17.3%) than PM10 (9.7%).